Social and ecological disparities in anaemia among adolescent girls 15-19 years old in Nepal - Anjana Rai; Mei Ting Chan; Smita Nambiar (Cambridge University Press, 2023)
Abstract Objective: Adolescent girls are at risk of anaemia due to increased nutrient demands because of growth, menstrual blood loss and possible pregnancies. Sociocultural and household conditions influence their anaemia risk. We aimed to identify the sociocultural and economic factors associated with anaemia among adolescent girls in Nepal. Design: The Nepal Demographic and Health Surveys (NDHS) conducted in 2006, 2011 and 2016 were pooled for secondary analysis. We used data on haemoglobin measurements for anaemia and conducted bivariate and multivariable logistic regression analyses to identify factors associated with anaemia. Setting: Nationally representative NDHS households with adolescent girls 15-19 years of age. Participants: Non-pregnant adolescent girls 15-19 years, with a haemoglobin measurement (n = 3731). Results: The overall prevalence of anaemia among adolescent girls was 39·6 %. Adolescents from socially disadvantaged caste/ethnicity groups were 1·42 times (95 % CI: 1·13, 1·78) more likely to have anaemia compared with those from Brahmin/Chhetri households. We found a counter-intuitive association between socio-economic status and anaemia where adolescents from the middle (adjusted OR (aOR) 1·37, 95 % CI: 1·01, 1·85) and highest (aOR 1·74, 95 % CI: 1·18, 2·56) quintiles were at increased odds of anaemia. Relative geographical inequality was observed where adolescents from the Terai region had 3·5 times (95 % CI: 2·32, 5·33) higher odds of anaemia. Conclusions: The disparities in the distribution of anaemia among adolescents by caste/ethnicity groups, wealth quintiles and geographical regions are evident. Reducing the anaemia burden will require addressing the social determinants of anaemia by allocating resources and expanding anaemia prevention programmes to target adolescents at higher risk.